Reinfection of SARS-CoV-2: reports of three cases from a tertiary care hospital of Bangladesh - Islam, Md Jubaidul; Ahmed, Jamal Uddin; Haque, Injamam Ull (BIRDEM Medical Journal, 2020)
Coronavirus disease 2019 (COVID-19) is a contagious respiratory and vascular disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). First identified in Wuhan, China, it has caused an ongoing pandemic. Some viruses give us lifelong immunity after first infection and initially researchers thought that SARS-CoV-2 infection may give lifelong immunity after first infection but few cases of reinfection are reported both locally and internationally. We report 3 symptomatic cases of reinfection, diagnosed clinically and confirmed by positive reverse transcriptase polymerase chain reaction (RT-PCR) for SARS-CoV-2. So, everybody who survived an infection of SARS-Cov-2, should maintain universal masking and social distancing. Birdem Med J 2020; 10, COVID Supplement: 107-110